Implementasi Sistem untuk Mendeteksi Jarak Aman Kendaraan Bermotor menggunakan Arduino dan Sensor Ultrasonik - Yonas Juniantiko Putro; Theophilus Wellem (Universitas Budi Darma, 2023)
Traffic accidents can occur due to driver error, natural factors (bad weather, heavy rain), or technical factors (for example, uneven roads or potholes). When driving a vehicle on the highway, a driver must always maintain a distance from the vehicle in front of it to reduce the risk of an accident. Likewise, when parking the vehicle, the driver must be able to maintain a distance from other objects around the vehicle so as not to crash into the object. To assist the driver in obtaining information about the vehicle's distance to the surrounding objects, this research designs and implements a system to detect the safe distance from a vehicle to other vehicles or objects in front of it. The hardware used in this system is an Arduino Uno R3 microcontroller board, an HC-SR04 ultrasonic sensor to measure distance, an LCD to display measurement results, and an LED and an electronic buzzer used as indicator and alarm when the distance is not safe. The test results show that the implemented system can measure the distance from a motorbike to objects in front of it and warns the driver by activating the LED and the buzzer if the distance is ranging 40 cm to 50 cm which indicates that the distance is not safe.